Implementation of Project Based Learning ‎in Teaching Speaking for 7th Grade Students - Josephine Marcela Setiawan; Sidik Indra Nugraha; Maya Rahmawati (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study aims to explore the implementation of Project-Based Learning (PBL) in teaching English speaking skills to seventh-grade students. A qualitative descriptive approach was employed, with data collected through classroom observations, teacher interviews, and documentation. The participants consisted of a class of seventh-grade students in an EFL context. The findings indicate that PBL was implemented through several stages, including preparation, planning, execution, monitoring, presentation, and reflection. The teacher played a significant role as a facilitator by providing scaffolding, guidance, and constructive feedback throughout the learning process. The use of technology, particularly video-based projects, helped reduce students’ speaking anxiety and encouraged active participation. However, several challenges were identified, such as time constraints, varying student abilities, and limited technological resources. Overall, the findings suggest that PBL can support student motivation, engagement, and speaking development when implemented with appropriate guidance and classroom management. This study offers practical insights for teachers and educators in applying PBL to enhance speaking instruction in EFL classrooms.